Transversus abdominis plane block in rats: Preliminary cadaveric studies. (February 2023) - Burrows, Chris S; Duncan, Juliet C; Martinez-Taboada, Fernando
The transversus abdominis plane (TAP) block is an ultrasound guided regional anaesthetic technique used to provide analgesia to the abdominal wall. Research in humans and cats has demonstrated that TAP blocks reduce pain and post-operative opioid requirements after abdominal surgery. To date TAP blocks have not been described in rats. The optimal technique to employ when performing TAP blocks is controversial with single point injection techniques failing to reliably provide adequate coverage of the cranial abdominal wall. It has been suggested that performing a two point injection may provide more reliable coverage of the cranial abdominal wall. The objective of this study was to determine the feasibility of performing ultrasound guided TAP blocks in rat cadavers and to evaluate whether performing a two point technique provides greater spread of injectate than a one point technique when administering the same total volume of methylene blue solution. Twenty-three, four-month-old, female Sprague Dawley rat cadavers weighing 506 ± 78 g were used. TAP blocks were performed using a total of 1 ml/kg of methylene blue solution. Overall success rates for injections were 21.7% (13.6–32.8%). Single point injection area of spread was 87.8 ± 32 mm 2 compared with 102.4 ± 17 mm 2 for the two point injection technique. Due to the low success rate the use of TAP blocks using the current technique cannot be recommended. Two point injection technique appears to provide greater spread; however, additional data is required to draw meaningful conclusions.